A Theoretical Approach to Customer Relationship Managment and Communication (Global Journal of Management and Business Research, 2015)
Nowadays customer relationship management process is a marketing approach used by various businesses. Management of customer relations provides businesses with great profits, especially in the case of gaining superiority in competition. This approach represents a process in the first place. It should be applied in an efficient and successful way by businesses. Moreover, ensuring customers' satisfaction while providing them with products and services plays a crucial role in increasing the profit rates. The efficiency level in communication among employees and customers forms one of the most important implementations enabling costumer satisfaction.
Keywords: customer; process of customer relationsip management; communication